Comparative politics 98/99 - Søe, Christian (The annual editions series, 1998)
Aims to provide access to articles selected from the best of the public press. Organizational features of this work include: an annotated listing of selected World Wide Web sites and table of contents; a topic guide; a general introduction; brief overviews for each section; an index; and an instructor's resource guide with testing materials.